KEHIDUPAN PEKERJA SEKS KOMERSIAL DI PERUMAHAN KUANTAN JAYA KECAMATAN TENAYAN RAYA. - Andra Eldino; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to determine the lives of sex workers before becoming commercial sex workers and their reasons for choosing work as commercial sex workers. In addition to knowing the management system or management of commercial sex workers, the form of their strategy in finding customers, and how they blend in with the surrounding community. This research is a qualitative descriptive study with a sample of 4 CSW’s. The selection of commercial sex workers is based on age, how long they have been commercial sex workers, and consultation with the head of the local RT. Data obtained by conducting direct interviews with CSW’s. Based on the results of the interview, before becoming a CSW, they were married. However, due to household problems (infidelity and the economy) that led to divorce, they chose to become a prostitute. Aside from being connected to their own lives, they also need to support their children and families. In arranging the process, the CSW’s are cared for by